2016
DOI: 10.1542/peds.2015-2741
|View full text |Cite
|
Sign up to set email alerts
|

The African Pediatric Fellowship Program: Training in Africa for Africans

Abstract: Africa has a significant burden of childhood disease, with relatively few skilled health care professionals. The African Paediatric Fellowship Programme was developed by the Department of Pediatrics and Child Health at the University of Cape Town to provide relevant training for African child health professionals, by Africans, within Africa. Trainees identified by partner academic institutions spend 6 months to 2 years training in the Department of Pediatrics and allied disciplines. They then return to their h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 19 publications
1
33
0
Order By: Relevance
“…29,71,98,110,122 Programs reported that retention of graduates was influenced by location of training as well as career prospects and employment opportunities after graduation. 8,10,66,74,79,92,98,[122][123][124][125][126][127] In several instances, tracking graduates of PGME programs revealed high rates of in-country retention, especially at academic centers. A study of academic faculty at a large hospital in Kenya reported the majority of surgeons on staff were trained locally.…”
Section: Thematic Analysis Of Lessons Learned From Specific Pgme Progmentioning
confidence: 99%
“…29,71,98,110,122 Programs reported that retention of graduates was influenced by location of training as well as career prospects and employment opportunities after graduation. 8,10,66,74,79,92,98,[122][123][124][125][126][127] In several instances, tracking graduates of PGME programs revealed high rates of in-country retention, especially at academic centers. A study of academic faculty at a large hospital in Kenya reported the majority of surgeons on staff were trained locally.…”
Section: Thematic Analysis Of Lessons Learned From Specific Pgme Progmentioning
confidence: 99%
“…In most parts of the world, children with epilepsy are not managed by child neurologists, let alone pediatric epilepsy specialists. Integrating epilepsy management into primary health care is an essential step to reduce the treatment gap and requires effective training programs . These programs should be aimed at training nonspecialist health care providers, and at empowering people with epilepsy and their caregivers for greater use of self‐ and home‐care programs …”
Section: Integrate Epilepsy Management Into Primary Health Carementioning
confidence: 99%
“…A newly qualified specialist trainee (ADD) commenced a pilot project with the African Paediatric Fellowship Programme (APFP) in the Department of Paediatrics and Child Health at UCT to address the task of training paediatric hospitalists. [5] The aim was to create a new 1-year fellowship curriculum, targeting trainees in the immediate post-accreditation period (equivalent to a 'year 5' following general paediatrics specialisation) and designed to address the issue of successful transitioning into the role of a hospital-based general paediatrics consultant, namely an ' African paediatric hospitalist' .…”
Section: The Pilot Programme Of the African Hospitalistmentioning
confidence: 99%